2007
DOI: 10.1002/jbm.b.30802
|View full text |Cite
|
Sign up to set email alerts
|

Development of self‐expandable covered stents

Abstract: We newly developed self-expandable covered stents by combining two of our original technologies. Of these, the first is the dip-coating covering method that was developed previously for balloon-expandable stents; the other is the newly developed self-expandable Nitinol stents, namely, Sendai stents. The three types of covered stents with the expansion diameter of 4.5, 5.0, or 6.0 mm thus obtained had a laser-processed microporous elastomeric cover film (pore diameter: 100 microm, interpore distance: 250 microm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Therefore, sustained release of the drug was expected after implantation. Recently, this drug has been used as an antithrombotic coating on blood‐contacting luminal surfaces of endovascular stents, where at 1 month after implantation, thin neointimal thickening with little thrombus formation was observed 11, 12. This study demonstrated the morphogenetic changes in vascular wall construction after implantation of biotubes, and the application of biotubes as small‐caliber vascular prostheses with diameters less than 2 mm was discussed.…”
Section: Introductionmentioning
confidence: 73%
“…Therefore, sustained release of the drug was expected after implantation. Recently, this drug has been used as an antithrombotic coating on blood‐contacting luminal surfaces of endovascular stents, where at 1 month after implantation, thin neointimal thickening with little thrombus formation was observed 11, 12. This study demonstrated the morphogenetic changes in vascular wall construction after implantation of biotubes, and the application of biotubes as small‐caliber vascular prostheses with diameters less than 2 mm was discussed.…”
Section: Introductionmentioning
confidence: 73%
“…The concept of the self‐expandable covered stent (stent coated with a segmented polyurethane film that was made microporous using KrF excimer laser)251 should be applied to both BMSs and DESs. In the latter, the luminal and outer surfaces of the microporous covered stent could be coated with drugs that have different actions, such as an antiproliferative agent and an anticoagulant.…”
Section: Areas/topics For Future Studymentioning
confidence: 99%
“…The work reported on the mathematical modeling of the elution of a protein from a composite core fiber/protein-loaded porous shell structure (a BRS) 169 should be expanded to the case when the bioactive agent was a drug, culminating in a validated mathematical model for the elution of a drug from a composite core fiber/drug-loaded microsphere shell structure. 99 The concept of the self-expandable covered stent (stent coated with a segmented polyurethane film that was made microporous using KrF excimer laser) 251 should be applied to both BMSs and DESs. In the latter, the luminal and outer surfaces of the microporous covered stent could be coated with drugs that have different actions, such as an antiproliferative agent and an anticoagulant.…”
Section: Stent Coating Materials and Drugsmentioning
confidence: 99%
“…Unfortunately, the synthetic materials originally used for covering small-caliber stents (Table 1) display limited hemocompatibility, and their use has resulted in restenosis, thrombotic [8,9] and inflammatory events [10,11]. Table 1: Materials employed for the fabrication of covered coronary stents and clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%